2002
DOI: 10.2337/diabetes.51.3.784
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of [U-13C]Palmitate Extracted by Skeletal Muscle in Subjects With Type 2 Diabetes and Control Subjects

Abstract: The current study investigated the fate of a [U-13 C] palmitate tracer extracted by forearm muscle in type 2 diabetic and control subjects. We studied seven healthy lean male subjects and seven obese male subjects with type 2 diabetes using the forearm muscle balance technique with continuous intravenous infusion of the stable isotope tracer [U-13 C]palmitate under baseline conditions and during intravenous infusion of the nonselective ␤-agonist isoprenaline (ISO; 20 ng ⅐ kg ؊1 lean body mass ⅐ min ؊1 ). In sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 22 publications
3
26
2
1
Order By: Relevance
“…The present data are not necessarily in contrast to previous findings, which generally show reduced NEFA uptake and/or oxidation rates over the leg or arm in recently diagnosed type 2 diabetes patients [11,14,16,20,45]. The greater whole-body NEFA turnover rate in long-termdiagnosed type 2 diabetes patients observed in the present study is most likely attributable to the presence of adipose tissue insulin resistance and the absence of compensating hyperinsulinaemia in the selected patient group.…”
Section: Discussioncontrasting
confidence: 84%
“…The present data are not necessarily in contrast to previous findings, which generally show reduced NEFA uptake and/or oxidation rates over the leg or arm in recently diagnosed type 2 diabetes patients [11,14,16,20,45]. The greater whole-body NEFA turnover rate in long-termdiagnosed type 2 diabetes patients observed in the present study is most likely attributable to the presence of adipose tissue insulin resistance and the absence of compensating hyperinsulinaemia in the selected patient group.…”
Section: Discussioncontrasting
confidence: 84%
“…It was initially reported that skeletal muscle fatty acid uptake in human muscle is reduced in type 2 diabetes (35,476). However, these observations are likely incorrect, because these conclusions appear to be based on problematic, indirect measurements, and the data do not concur with more recent direct determination of fatty acid transport rates across the plasma membrane in muscles of diabetic animals (71,387) or humans with type 2 diabetes (48).…”
Section: Human Studiesmentioning
confidence: 52%
“…Skeletal muscle oxidative capacity, on the other hand, has been shown to be predictive of insulin action when sedentary and physically active individuals are studied (16). A reduction in fatty acid oxidation in skeletal muscle has been reported in obese and type 2 diabetic individuals in postabsorptive conditions (9,10,65,112). This observation is more controversial when subjects are performing exercise where whole body fat oxidation has been found to be either reduced (86) or increased (14,15,37) compared with lean control.…”
Section: Relationship Between Imtg and Insulin Resistance In Humansmentioning
confidence: 75%